Barriers to Integration of Traditional and Complementary Medicine in Supportive Cancer Care of Arab Patients in Northern Israel. (1st December 2011) - Ben-Arye, Eran; Steiner, Mariana; Karkabi, Khaled; Shalom, Tamar; Levy, Levava; Popper-Giveon, Ariela; Schiff, Elad
Abstract : In 2008, an Integrative Oncology Program (IOP), aiming to improve patients' quality of life during chemotherapy and advanced cancer, was launched within the Clalit Health Organization's oncology service at the Lin Medical Center, Haifa, Israel. The IOP clinical activity is documented using a research-based registry protocol. In this study, we present an analysis of the registry protocol of 15 Arab patients with cancer who were referred to the IOP. Analysis of patients' reported outcomes using the Edmonton Symptom Assessment Scale suggests that integrative medicine care improves fatigue (P = 0.024 ), nausea (P = 0.043 ), depression (P = 0.012 ), anxiety (P = 0.044 ), appetite (P = 0.012 ), and general well-being (P = 0.031 ). Barriers to integration of traditional and complementary medicine in supportive care of Arab patients are discussed followed by six practical recommendations aimed at improving accessibility of patients to integrative supportive care, as well as compliance with treatments.